Role of mass effect and trehalose on early erythrolysis after experimental intracerebral hemorrhage. Issue 1 (18th April 2021) - Gong, Yuhua; Ren, Peng; Deng, Jia; Hou, Zongkun; Guo, Tingwang; Hao, Shilei; Wang, Bochu
Abstract: The mechanisms of brain injury after intracerebral hemorrhage (ICH) involve mass effect‐induced primary injury and secondary injury caused by a pathologic response to the hematoma. Considerable attentions have recently been paid to the mechanisms and therapeutic strategy for secondary brain injury due to no overall benefit from early surgery compared with initial conservative treatment. However, it is unclear whether there is a causal relationship between mass effect and secondary brain injury. Here, the role of mass effect on early erythrolysis after experimental ICH was investigated based on the poly( N ‐isopropylacrylamide) (PNIPAM) ICH model. Autologous blood and PNIPAM hydrogel were co‐injected into the right basal ganglia of rats to induce different degrees of mass effect, but with a constant hematoma. The influences of different mass effect and time courses on erythrolysis and brain damages after ICH were investigated. Furthermore, the protective effect of trehalose against erythrolysis after ICH was evaluated. The results showed that mass effect caused erythrocyte morphological change at 24 hr after ICH. The released hemoglobin was quantitatively evaluated by a polynomial concerning with the mass effect, the volume of hematoma, and the time of ICH. An obvious increase in heme oxygenase‐1 (HO‐1) and ionized calcium binding adaptor molecule‐1 (Iba‐1) expression, iron deposition, cell death, and neurological deficits was observed with increasing mass effect. Moreover, trehalose alleviated brain injury by inhibiting erythrolysis after ICH. These data demonstrated that mass effect accelerated the erythrolysis and brain damages after ICH, which could be relieved through trehalose therapy. Abstract : We demonstrated the deteriorating effect of mass effect on early erythrolysis after intracerebral hemorrhage (ICH). Mass effect induced obvious early erythrocyte morphological change and hemoglobin release, heme oxygenase‐1 (HO‐1) upregulation, macrophage/microglia activation, iron deposition, cell death and neurological deficits. The released hemoglobin could be quantitatively evaluated by a polynomial related to the mass effect, volume of hematoma and the time of ICH. Moreover, trehalose could alleviate brain injury through inhibiting erythrolysis after ICH. These findings were expected to provide new strategies for ICH mechanism research and intervention.